AN ANALYSIS OF THE FIRST YEAR STUDENTS’ ABILITY IN COMPREHENDING DESCRIPTIVE TEXT ON HERITAGE AT MTsN 1 DUMAI - Nurjihah Nurjihah; Fakhri Ras; Jismulatif Jismulatif (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study is to find out the ability and the level of the first year students’ ability in comprehending descriptive text on heritage at MTsN 1 Dumai. The ability is about comprehending descriptive text on heritage in general and for each components of reading comprehension in terms of finding main ideas, factual information, the meaning of difficult words, finding reference and finding restatement. Before administering the test, it was tried out in class. Its purpose is to check the validity and reliability of the test. The data were collected by using descriptive text on heritage test in the form of multiple choice. The test contained 5 texts with 25 items. Based on the data analysis, it was found out that: the ability of the first year students in comprehending descriptive text on heritage in general is in good level with the mean score of 71.55. Then, the students’ mean score in finding the main idea is in excellent level with the mean score of 85. While, finding the factual information is in excellent level with the mean score of 90. Finding the meaning of difficult words is in average level with the mean score of 55.55. The next is finding reference is in good level with the mean score of 60. Finding restatement is in good level with the mean score of 66.66. Based on the findings of this study, it can be suggested that the students should learn more seriously on the part of meaning of difficult words which deal with the comprehend ability of descriptive text on heritage.Key Words: Analysis, Ability, Descriptive text, Heritage.